Cuban professors, teaching Medicine, in an Arabic country, in English - Agustín Vicedo Tomey (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Cuban medical collaboration has not been limited to the field of health care, it has also included the training of own human resources, including the creation of Medical Faculties in other countries. The Faculty of Medicine of the Democratic Republic of Yemen is a leading example of this activity. Objective: To describe some characteristics and singularities of this relevant historical event of the Cuban medical collaboration. Material and Methods: A descriptive historical research was done, based on journalistic materials, photographs, personal diary and other documents of the author's archives. Development: The Faculty of Medicine of Aden was created in 1975 with the participation of Cuban professors as collaborators. During its second course, this Faculty received the visit of Commander-in-Chief Fidel Castro Ruz during his stay in the Democratic Republic of Yemen in March of 1977. The Yemeni press provided a wide coverage to the visit. Fidel had words of encouragement and admiration for the accomplishment of this collaboration. Conclusions: The creation of the Faculty of Medicine in the Democratic Republic of Yemen in 1975 was an important historical milestone in the development of Cuban medical collaboration. Fidel Castro's visit to the Faculty of Medicine in Aden in March 1977 was a stimulus of special significance for Cuban collaborators. Keywords: Medical collaboration, medical education, international cooperation, relevant history point.